Janus particles for biological imaging and sensing. Issue 12 (7th April 2016) - Yi, Yi; Sanchez, Lucero; Gao, Yuan; Yu, Yan
Abstract : Janus particles with anisotropic surface makeup or compartments enable novel imaging and sensing in biological systems. Abstract : Janus particles, named after the two-faced Roman god Janus, have different surface makeups, structures or compartments on two sides. This review highlights recent advances in employing Janus particles as novel analytical tools for live cell imaging and biosensing. Unlike conventional particles used in analytical science, two-faced Janus particles provide asymmetry and directionality, and can combine different or even incompatible properties within a single particle. The broken symmetry enables imaging and quantification of rotational dynamics, revealing information beyond what traditional measurements offer. The spatial segregation of molecules on the surface of a single particle also allows analytical functions that would otherwise interfere with each other to be decoupled, opening up opportunities for novel multimodal analytical methods. We summarize here the development of Janus particles, a few general methods for their fabrication and, more importantly, the emerging and novel applications of Janus particles as multi-functional imaging probes and sensors.